Notices - Hughes, Ian (LiNQ (Literature in North Queensland), 2016)
A series of recommendations and notes on recent publications. Whole Earth Epilogue Index of Possibilities: Energy and Power, Penguin Real Time: A Caralogue of Ideas and Information, Picador Any Old Way You Choose It, Robert Christgan, Penguin Rock File, Rock File 2, Charles Gillett, Panther Writings and Drawings, Bob Dylan, Panther Song and Dance Man; The Art of Bob Dylan, Abacus Bob Dylan: A Retrospective, Craig McGregor, Angus & Robertson Bound for Glory, Woody Guthrie, Paladin The Mountain People, Colin Turnbull, Picador Athies. Achdiat K Michardja, UQP Tropical Gothic, Nick Joaquin, UQP Padma River Boatman, Manik Bandopadhyaya, UQP Black Writing from New Guinea, Editor Ulli Beier, UQP Contemporary Indonesian Poetry, UQP A Heap of Ashes, UQP A Thousand Miles Away: A History of North Queensland to 1920, GC Bolton Lectures on North Queensland History, History Department, James Cook University